A comparison of postoperative blood lactate concentrations and kinetics in cardiac surgical patients being and not being administered metformin - Ampatzidou, Fotini; Diplaris, Konstantinos; Drosos, Odysseas; Drossos, George (Journal of Medical Science, 2022)
Aim. Early discontinuation of metformin before cardiac surgery is advised by several national societies, although no hard evidence exist supporting this practice. This precaution is mostly extrapolated by data on different clinical settings. The aim of this study is to investigate the impact of preoperative metformin use on lactate concentrations and lactate clearance during the first postoperative day following cardiac surgery. Methods. Among 367 consecutive patients who underwent elective on-pump cardiac surgery from January 2019 to October 2019, 109 were diabetics, 74 of whom were treated with metformin. Data on lactate concentrations and clearance during the first postoperative day were prospectively collected on arrival in the ICU, as well as after H6, H12 and H24 in the ICU and subsequently compared. A subgroup analysis focusing only on the diabetic patients was also performed. Repeated measures multivariate analysis of variance (MANOVA) was used to investigate the data on the basis of the group, time and their interaction effects. Results. Lactate concentrations were the same for both groups upon arrival in the ICU. Interestingly, metformin users presented lower lactate concentrations than non-users on the following measurements (p = 0.003 at 6 h and p = 0.01 at 24 h). No significant interaction was found between the two groups (p = 0.76). No difference was found between the two groups in terms of lactate clearance (p = 0.53). In the subgroup analysis no difference was observed between metformin users and non-users, either on lactate concentrations (p = 0.61), or on lactate clearance (p = 0.86). Conclusions. In the intensive care unit setting following heart surgery, the use of metformin up until the night before surgery was not associated with increased postoperative lactate concentrations or impaired lactate clearance.